A CMOS-Compatible, Low-Noise ISFET Based on High Efficiency Ion-Modulated Lateral-Bipolar Conduction - Hsin Chen; Sheng-Ren Chang (Sensors, 2009)
Ion-sensitive, field-effect transistors (ISFET) have been useful biosensors in many applications. However, the signal-to-noise ratio of the ISFET is limited by its intrinsic, low-frequency noise. This paper presents an ISFET capable of utilizing lateral-bipolar conduction to reduce low-frequency noise. With a particular layout design, the conduction efficiency is further enhanced. Moreover, the ISFET is compatible with the standard CMOS technology. All materials above the gate-oxide are removed by simple, die-level post-CMOS process, allowing ions to modulate the lateral-bipolar current directly. By varying the gate-to-bulk voltage, the operation mode of the ISFET is controlled effectively, so is the noise performance measured and compared. Finally, the biasing conditions preferable for different low-noise applications are identified. Under the identified biasing condition, the signal-to-noise ratio of the ISFET as a pH sensor is proved to be improved by more than five times.